Neurodevelopmental defects in Dravet syndrome Scn1a+/− mice: Targeting GABA-switch rescues behavioral dysfunctions but not seizures and mortality - Lara Pizzamiglio; Fabrizio Capitano; Evgeniia Rusina; Giuliana Fossati; Elisabetta Menna; Isabelle Léna; Flavia Antonucci; Massimo Mantegazza (Neurobiology of Disease)
Dravet syndrome (DS) is a developmental and epileptic encephalopathy (DEE) caused by mutations of the SCN1A gene (NaV1.1 sodium channel) and characterized by seizures, motor disabilities and cognitive/behavioral deficits, including autistic traits. The relative role of seizures and neurodevelopmental defects in disease progression, as well as the role of the mutation in inducing early neurodevelopmental defects before symptoms' onset, are not clear yet. A delayed switch of GABAergic transmission from excitatory to inhibitory (GABA-switch) was reported in models of DS, but its effects on the phenotype have not been investigated.Using a multi-scale approach, here we show that targeting GABA-switch with the drugs KU55933 (KU) or bumetanide (which upregulate KCC2 or inhibits NKCC1 chloride transporters, respectively) rescues social interaction deficits and reduces hyperactivity observed in P21 Scn1a+/− DS mouse model. Bumetanide also improves spatial working memory defects. Importantly, neither KU nor bumetanide have effect on seizures or mortality rate. Also, we disclose early behavioral defects and delayed neurodevelopmental milestones well before seizure onset, at the beginning of NaV1.1 expression.We thus reveal that neurodevelopmental components in DS, in particular GABA switch, underlie some cognitive/behavioral defects, but not seizures. Our work provides further evidence that seizures and neuropsychiatric dysfunctions in DEEs can be uncoupled and can have differential pathological mechanisms. They could be treated separately with targeted pharmacological strategies.